Comparing the effects of typical and atypical antipsychotics on serum lipid and liver enzyme levels - Kulo?lu, Murat; Albayrak, Yakup; Ekinci, Okan; Önen, Sinay; Çayköylü, Ali (My University, 2010)
Purpose: In this study, it is aimed to compare the alterations of serum lipid levels and hepatic enzymes associated with typical and atypical antipsychotic drugs in psychiatric patients. Method: Chart reviews of inpatients followed-up at Psychiatry Department of Ankara Ataturk Education and Research Hospital from January 2008 to January 2009 were examined in detail. Ninety eight (44 male and 54 female) patients whose baseline and follow-up lipid profiles (LDL, HDL, triglyceride, total cholesterol) and liver function tests including ALT, AST, GGT and LDH that were measured before and after the treatment period of one month and who had not used any drug less than one week (or not administrated depot antipsychotics less than one month) were enrolled to the study. Findings: The repartition according to treatment is as follows: olanzapine (n=34), risperidone (n=15), and quetiapine (n=15), aripiprazole (n=12) and typical antipsychotics (n=22). There is no significant increase in AST, GGT and LDH enzyme levels between the typical and atypical antipsychotics at the end of the first month of study. It was also observed, there is a significant increase of ALT level in the group of olanzapine. While there was a significant increasing in serum triglyceride and total cholesterol levels in typical antipsychotic and olanzapine groups after treatment, it was revealed no significant difference in other antipsychotic groups. Although significant weight gain was detected after treatment in all antipsychotic groups, it was found most in olanzapine taking group. Discussion and Conclusion: Schizophrenic patients have more cardiovascular risk factor compared with normal population. Therefore, it is required to be careful when choosing an antipsychotic in the schizophrenic patients with dyslipidemia and obesity. Also, our findings suggest that olanzapine in short-term treatment may lead to evidence of asymptomatic liver function test abnormalities, however, it rarely may cause marked liver function test abnormalities at therapeutic doses. Therefore, evaluating the liver enzymes in patients who use antipsychotics in regular intervals seems to be important.
Tipik ve atipik antipsikotiklerin serum lipid ve karaci?er enzim düzeyleri üzerine etkilerinin karşilaştirilmasi
Keywords: Antipsychotics; Lipid levels; Liver enzyme levels; Schizophrenia